Postpartum Stanford type B aortic dissection in a woman with Loeys-Dietz syndrome who underwent a prophylactic aortic root replacement before conception: A case report - Rieko Shitara; Takayuki Iriyama; Seisuke Sayama; Norifumi Takeda; Takeshi Nagamatsu; Yutaka Osuga; Tomoyuki Fujii (Elsevier, 2021)
Objective: Loeys-Dietz syndrome (LDS) is associated with a higher risk of aortic dissections (ADs) during pregnancy and postpartum. However, there is limited evidence about the perinatal management of LDS patients who have undergone prophylactic aortic root replacements (ARRs) before conception. Case report: We present the case of a 28-year-old nulliparous pregnant woman with LDS with a pathogenic variant within exon 5 of TGFBR2 (c.1379G > T, p.[Arg460Leu]), who underwent an ARR at 20 years of age. Cardiac echocardiography did not show any significant changes in the aorta during pregnancy, and her blood pressure remained normal. She had a cesarean section at 37 weeks of gestation. She developed an acute Stanford type B AD extending from the aortic arch to the infrarenal aorta 8 days postpartum and underwent a total arch replacement. Conclusion: This case report suggests that patients with LDS after prophylactic ARRs still possess a risk for Stanford type B ADs.